Surgical repair for abductor lesion after revision total hip arthroplasty: a systematic review. Issue 4 (July 2020) - Di Martino, Alberto; Geraci, Giuseppe; Stefanini, Niccolò; Perna, Fabrizio; Mazzotti, Antonio; Ruffilli, Alberto; Faldini, Cesare
Background: Abductor mechanism lesions represent a severe complication after revision total hip arthroplasty (rTHA). The resulting abductor insufficiency can cause limping, pain, instability, and a higher rate of failure, thus requiring further revision surgery. In case of severe degeneration and retraction of the abductor mechanism, several different surgical treatments are needed. Aim: To systematically review all studies reporting on surgical treatment of severe abductor lesion after rTHA, focusing on surgical techniques, and clinical and functional results. Method: Scientific databases were accessed in December 2018 to identify studies addressing the surgical management of severe abductor disruption after rTHA. The PRISMA guidelines were followed. Data were extracted from the identified articles and summarised. Only data about patients with symptoms of abductor insufficiency after rTHA were included in the database. Results: 9 retrospective studies were included, all being retrospective case series reporting on a total of 92 patients. Several surgical strategies have been described and performed: a repair using a synthetic mesh was reported in 1 study; 2 studies reported on local muscle transfer (gluteus maximus transfer or advancement); vastus lateralis advancement was described in 4 studies while in 2 studies the injury was repaired with the use of an allograft. Overall positive results have been reported in terms of pain reduction, while poor to mild functional scores with persistent limping have often been observed in the postoperative period. Conclusions: The short follow-up time of the reviewed studies is inadequate to uncover any late dislocation, implant failure or different complications related to abductor mechanism reconstruction.